2021
DOI: 10.1038/s41419-021-04313-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid receptor 2 alleviates glucocorticoid-induced osteonecrosis of femoral head with osteogenesis and maintenance of blood supply

Abstract: In glucocorticoid (GC)-induced osteonecrosis of the femoral head (ONFH), downregulated osteogenic ability and damaged blood supply are two key pathogenic mechanisms. Studies suggested that cannabinoid receptor 2 (CB2) is expressed in bone tissue and it plays a positive role in osteogenesis. However, whether CB2 could enhance bone formation and blood supply in GC-induced ONFH remains unknown. In this study, we focused on the effect of CB2 in GC-induced ONFH and possible mechanisms in vitro and in vivo. By using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…These results suggest that osteoblast apoptosis is induced by corticosteroids via the PI3K/ACT/FOXO1 signaling pathway. Sun et al also examined the effects and possible mechanisms of cannabinoid receptor 2 (CB2) in steroid‐induced ONFH, which studies have suggested to play an essential role in promoting bone formation 60 . Activation of CB2 promoted the GSK‐3β/β‐catenin signaling pathway, resulting in enhanced osteogenic activity of BMSCs, even under the influence of corticosteroids.…”
Section: Preclinical In Vitro Studiesmentioning
confidence: 99%
“…These results suggest that osteoblast apoptosis is induced by corticosteroids via the PI3K/ACT/FOXO1 signaling pathway. Sun et al also examined the effects and possible mechanisms of cannabinoid receptor 2 (CB2) in steroid‐induced ONFH, which studies have suggested to play an essential role in promoting bone formation 60 . Activation of CB2 promoted the GSK‐3β/β‐catenin signaling pathway, resulting in enhanced osteogenic activity of BMSCs, even under the influence of corticosteroids.…”
Section: Preclinical In Vitro Studiesmentioning
confidence: 99%
“…The results of H&E staining were the same as those of Mirco-CT, indicating PACs had a protective effect against the loss of bone trabeculae in MPS-induced femoral head necrosis (Figure 2A,B). Decalcification will cause certain empty bone traps, but the rate is low; generally, normal bone tissue decalcification caused by empty bone traps does not exceed 10%, whereas the rate of empty bone traps in necrotic tissue can reach 40-80% [24]. Femoral head tissues were also examined for apoptosis using TUNEL staining, and the finding demonstrated that the control group had the least number of positive cells.…”
Section: Proanthocyanidins Treat Early Dex-induced Bone Loss By Inhib...mentioning
confidence: 99%
“…According to the “BMSCdifferentiation theory”, high concentrations of GCs can inhibit osteogenesis and promote BMSC adipogenesis, reduce bone formation, and disrupt bone remodeling as well as cartilage metabolism, leading to severe necrosis and collapse of the femoral head. [ 5 ] Furthermore, according to the “cell apoptosis theory”, high doses of GCs can directly induce apoptosis of osteoblasts, osteocytes, and bone marrow stromal cells, the accumulation of which is the main characteristic of ONFH and leads to irreversible damage, necrosis, or even collapse of the femoral head. [ 6 ] As such, reversing osteogenesis dysfunction and apoptosis of BMSCs in the early stages of ONFH may be a suitable approach for curing ONFH.…”
Section: Introductionmentioning
confidence: 99%